Zeolite and Charcoal as Potential Adsorbents in Tubs of Oxydation Ditch I and Oxydation Ditch II at Water Treatment and Composting Plant (WTCP) PT. Djarum Kudus - Rissa Kharismawati; Redi Joko Prasetyo; Yayuk Astuti (Jurnal Kimia Sains dan Aplikasi, 2018)
This study aims to determine the mass of zeolite and charcoal required as lime nutrient adsorbent (Ca(OH)2) in reducing pH, TSS, COD, and SV values in tubs of oxidation of ditches I and II in Water Treatment and Composting Plant (WTCP) PT. Djarum Kudus with the principle of adsorption. The methods used were jar test and spectrophotometry. The adsorbents used were chalk (Ca(OH)2), zeolite, and charcoal added to the tub samples of oxydation ditch I and oxidation ditch II by variation of mass for every adsorbent, that were 2 gram, 4 gram and 6 gram. The results showed that zeolite and charcoal were more effective than charchoal in lowering pH, COD, TSS and SV values in tubs of oxidation ditches I and II on the addition of 6 gram in 500 ml of sample.